Opioid-Free Perioperative Analgesia for Revision Total Hip Arthroplasty in a Patient With a History of Substance Use Disorder - Robert L. Owen; Mitchell J. Kerfeld; Jason K. Panchamia; David A. Olsen; Adam W. Amundson (Case Reports in Anesthesiology)
Conclusions: Complimentary regional nerve blocks, when combined with surgeon-administered local infiltration analgesia and multiple systemic nonopioid medications, can provide sufficient analgesia to cover the complexly innervated hip joint and accomplish an opioid-sparing revision total hip arthroplasty perioperative course.